1998
DOI: 10.4315/0362-028x-61.6.738
|View full text |Cite
|
Sign up to set email alerts
|

Survey of the Occurrence of Aflatoxin M1 in Dairy Products Marketed in Italy

Abstract: During 1995, 159 samples of milk, 97 samples of dry milk for infant formula, and 114 samples of yogurt were randomly collected in supermarkets and drug stores in four large Italian cities and checked for aflatoxin M1 (AFM1) by immunoaffinity column extraction and HPLC. AFM1 was detected in 136 (86%) of the milk samples (in amounts ranging from < 1 ng/liter to 108.5 ng/liter; mean level: 10.19 ng/liter), in 81 (84%) of the dry milk samples (in amounts ranging from < 1 ng/liter to 101.3 ng/kg; mean level: 21.77 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
29
2
6

Year Published

1999
1999
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(44 citation statements)
references
References 0 publications
7
29
2
6
Order By: Relevance
“…In comparison with recent data reporting the incidence of AFM 1 reported by others investigators (3,4,5,9,10,11,15,17,19,25) the results of this study are comparable with those presented in other countries, showing high incidence at low levels. According to Galvano et al (4), in recent years the incidence of AFM 1 has been balanced on the one hand by the higher efficiency of analytical methods, and on the other hand by the setting of a stricter regulatory limit for aflatoxins in feed and milk.…”
Section: Shundo and M Sabinosupporting
confidence: 79%
“…In comparison with recent data reporting the incidence of AFM 1 reported by others investigators (3,4,5,9,10,11,15,17,19,25) the results of this study are comparable with those presented in other countries, showing high incidence at low levels. According to Galvano et al (4), in recent years the incidence of AFM 1 has been balanced on the one hand by the higher efficiency of analytical methods, and on the other hand by the setting of a stricter regulatory limit for aflatoxins in feed and milk.…”
Section: Shundo and M Sabinosupporting
confidence: 79%
“…The results of this study revealed that twelve species isolated from 100 samples of crude milks collected from The incidence of AFM1 and AFM2 observed in the present study was higher than the incidence of AFM1 and AFM2 reported by other authors [Galvano et al, 1998, kim et al, 2000, Rossi et al,. 2002.…”
Section: Resultscontrasting
confidence: 55%
“…The incidence of AFM 1 in 114 samples of yoghurt collected from four large Italian cities has been reported by Galvano et al (1998). They observed that 91 (80%) samples were contaminated with AFM 1 ; and only two (1.8%) samples were above the 0.050 lg/l.…”
Section: Yoghurtmentioning
confidence: 89%